Profile Matching in Government Scholarship Acceptance System for Student in Aceh Utara - Sujacka Retno; Novia Hasdyna (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
The scholarship program held to ease the burden of students in taking the study period, especially in terms of costs. This research conducted at SMP Negeri 7 Sawang – Paya Gaboh in Sawang sub-district, Kabupaten Aceh Utara. This research discusses the provision of educational scholarships from the government of Kabupaten Aceh Utara for students. Therefore, the researcher intends to offer a solution to determine the scholarship recipients at SMP Negeri 7 Sawang by applying the Profile Matching method to find the criteria for receiving the scholarship. The purpose of this research is to design and build a system to determine students who are entitled to receive the scholarships by applying the Profile Matching method based on core data and secondary factors. The implementation of the results of the criteria for the scholarship recipients will be processed using the Profile Matching method. It will produce an output that later assist the selection team in finding the scholarship recipients. The results of the research indicate that the use of the Profile Matching algorithm in finding scholarship recipients works according to the expected categories. The student with the highest score on rank is the first alternative that deserves to be the recipient of the government scholarship aid of Kabupaten Aceh Utara. The system is builtand implemented using PHP programming language.